Middleton's allergy : principles and practice - Burks, A. Wesley; Holgate, S. T; O'Hehir, Robyn E; Broide, David H; Bacharier, Leonard B; Khurana Hershey, Gurjit K; Peebles, R. Stokes (Elsevier, 2020)
The 9th Edition covers all basic science and clinical applications regarding allergy practice and disease mechanisms. It brings you up to date with recent innovations in the diagnosis, prevention, and management of allergic disorders. For clinicians and researchers as both a practical reference and an effective self-assessment tool for board preparation.
Keywords: imunita; Hypersensitivity; Immunity; alergie; alergologie a imunologie